FREQUENCY OF ATRIAL FIBRILLATION IN PATIENTS WITH ACUTE ISCHEMIC STROKE - Ashok Kumar Lohano1 , Basra Qazi2 , Nazia Arain3 , Shaharyar4 , karishma Sahetiya5 , Twinkle Kukreja6 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2022)
ABSTRACT Introduction: Acute ischemic stroke (AIS) has many preventable causes; of which atrial fibrillation (AF) is a significant issue. Varying frequencies of AF among stroke patients have been reported. The discrepancy is majorly due to hindrances in detection of intermittent and silent AF. This study aimed to determine the frequency of Atrial Fibrillation (AF) in patients presenting with acute ischemic stroke. Objective: To determine the frequency of atrial fibrillation in patients with acute ischemic stroke visiting peoples medical college and hospital (PMCH), Nawabshah. Methods: A cross-sectional, observational study was conducted in the Department of General Medicine, (Unit III) at Peoples Medical College and Hospital, Nawabshah. Study duration was from 4 th Aug 2020 to 4th Feb 2021. All patients with acute ischemic stroke were included. Sociodemogrpahic profile was documented. Occurrence of atrial fibrillation was recorded on electrocardiogram was done ill these patients to reach the outcome i.e. frequency of AF. Data was entered and analyzed using SPSS v.22. Result: Of 183 ischemic stroke patients, there were 104 (56.8%) males and 79 (43.2%) females. Their mean age (years) was 50.19 ± 7.33. Atrial fibrillation was seen in 45 (24.6%) patients. Most AF patients were males, older in age and had a statistically significant family history of AIS. Conclusion: This study concludes that AF patients are a high-risk group for developing acute ischemic stroke episodes. The incidence is higher in male gender, older population, and individuals with family history of ischemic stroke.